Stacking tests and finite element analysis of sandwich structure plastic containers - Jón Þór Backman 1993- (2020)
This work presents a study on the feasibility of using finite element analysis to assist with the design of new sandwich layered (polyethylene / expanded polyethylene (foam) / polyethylene) plastic containers. The motivation for this project is the high cost that incurs from the destructive tests of prototypes while developing new products. To make sure that the finite element analysis yields reliable results, theoretical calculations and destructive stacking tests are made to calibrate the models. To increase the accuracy of the models, different types of elements and mesh densities are tried, and primary material properties are tested for both polyethylene and expanded polyethylene. For the finite element analysis to be useful the models must be able to show where the highest probability of failure will occur and for the error to be in single digits as of high variance in mechanical properties of polyethylene. The analysis offered promising results, showing high stress in the same areas that the destructive stacking tests did with variances well under double digits; offering valuable information for the development of new products. Technology Development Fund (project no. 164698-061) AVS R&D Fund of Ministry of Fisheries and Aquaculture in Iceland (project no. R 016-17) Saeplast Iceland iTub